Economic growth and pollution in different political regimes - Andreas Kammerlander (University of Freiburg, Department of International Economic Policy (iep), 2022)
I examine the association between nighttime light luminosity and ten pollution measures (CO2, CO, NOx,SO2, NMVOC, NH3, BC, OC, PM10 and PM2.5) across different political regimes at a local level. Although the effects of the political system and economic growth on pollution have been widely analyzed at the country level, this is the first study to do so at the grid level. The empirical analysis yields three major insights. First, economic growth is positively associated with a wide array of different pollution measures. Second, there are significant differences in the association between economic growth and air pollution across different political regimes. For example, the association between nighttime light luminosity and air pollution is strictly positive for autocracies. The association between nighttime luminosity and air pollution is substantially smaller but still positive for democracies. Furthermore, among democracies the relationship between nighttime light luminosity and air pollution is concave for nine out of ten pollutants; among autocracies, the relationship is either convex (five out of ten pollutants) or the squared term is insignifcant. Third, the differences among political regimes is driven chiefly by pollution emissions in the industry, energy, and transport sectors; there is no difference between autocracies and democracies in terms of the effect of growth on emissions in the agricultural and residential sectors.
Keywords: O18; Q53; 330; local economic growth; air pollution; nighttime lights; geo-data